RENTANG MASA DAN BUDAYA MANDAILING PADA PUSTAHA LAKLAK DAN NASKAH BAMBU DI BAGAS GODANG HUTA GODANG, MANDAILING NATAL - Churmatin Nasoichah; Nenggih Susilowati; Andri Restiyadi (Berkala Arkeologi Sangkhakala, 2021)
The Mandailing people have a writing habit that develops in their region. The influence of Hindu-Buddhist culture has influenced the culture of writing in the communities around the area. The use of written sources with local characters, one of which is found in Bagas Godang Hut Godang, Kec. Ulu Pungkut, Mandailing Natal. From the results of the research that has been carried out, it is not certain that the time span of making and using these manuscripts by the Mandailing people in the past cannot be ascertained. Through this background, the research problem is related to the span of time of making and using pustaha laklak and bamboo manuscripts stored in godang huta Godang bagas, Ulu Pungkut District, Mandailing Natal Regency, North Sumatra. Besides that, what is the description of the Mandailing community during that period. The research method used is qualitative research methods. From the analysis, it is known that pustaha laklak A-2/2014 was made and used in the range of 1720 - 1890 AD and the bamboo manuscript B-5/2014 was made and used in the range of 1790 - 1950 AD. The existence of pustaha laklak A-2/2014 and bamboo manuscripts B-5/2014 is proof that in the 18-20s AD the Mandailing region was still a small kingdom consisting of several huta (villages).